TRUTHS AND CURIOSITIES IN THE HISTORICAL DICTIONARIES OF THE EAST SLAVIC LANGUAGES OF THE 20th AND 21th CENTURIES - Andrash Zoltan (Вестник Московского государственного областного университета, 2017)
The article analyses the interesting cases of the wrong reading and interpretation of lexical items in the dictionaries of East Slavic languages of the XX-XXI centuries. The author by the historical-linguistic, etymological and cultural analysis of the «dark places» and gaps, as well as of the realities of their existence in the texts, restores the true picture of word existence, clarifies and reconciles its semantics. So, analysing the dictionary entry «income» containing some misinformation in the «Dictionary of the Old Russian language (XI–XIV centuries)», the author shows the nature of the borrowed word in the Russian language. There are also examples of misinterpretation of the following lexemes: kma(t) instead of k[a]mat’ and polski ‘relating to Poland’ instead of the correct meaning ‘field’. Such cases will allow modern researchers of written records to refer to reliable sources and understand the importance of learning lexicographic material not only from the point of view of obtaining background information, but it will help to identify mistakes and errors.